2004
DOI: 10.1023/b:jose.0000038451.04626.18
|View full text |Cite
|
Sign up to set email alerts
|

The Marmara Sea region: Seismic behaviour in time and the likelihood of another large earthquake near Istanbul (Turkey)

Abstract: The North Anatolian Fault (NAF) extends for about 1500 km from Karliova to the east, to the Egean Sea in the west. The Marmara region, located near the western end of the NAF, is a tectonically active zone characterized by the transition between a strike slip stress regime and an extensional one in the Aegean Sea. Microseismic studies performed around the Marmara Sea in 1995 [Tectonophysics 316, 2000, 1], and just before the 1999 Izmit Earthquake (Bull. Seism. Soc. Am. 92, 2002a, 361; J. Seismol. 6, 2002b, 287… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Refs. [15,10,3,6,18,2]. Each research group constructed their own time series for the R/S analysis from the earthquake catalogue.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Refs. [15,10,3,6,18,2]. Each research group constructed their own time series for the R/S analysis from the earthquake catalogue.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
“…Telesca et al [18], for example, had analyzed the temporal fluctuations of the Hurst exponent H for the waiting time of the earthquakes occurred in southern Italy and found the values of H range from 0.5 to 0.92 with a mean of 0.74. Cisternas et al [2] had constructed the cumulative seismic moment as a function of time for conducting the R/S analysis of the seismicity in the Marmara Sea Region, Turkey, and concluded that the aftershocks of the 1999 Izmit earthquake show an exceptionally high persistent memory with the H of 0.95.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have comprised reassessment of historical seismicity (Ambraseys and Jackson 2000;Ambraseys 2001aAmbraseys , b, 2002a, monitoring of microseismicity (Sato et al 2004), high-resolution bathymetry and multi-channel seismic reflection studies (Okay et al 2000;Le Pichon et al 2001;Armijo et al 2002Armijo et al , 2005Parke et al 2002;Gökaşan et al 2003;Demirbag et al 2003;McHugh et al 2006;Kanbur et al 2007), earthquake focal mechanism-derived stress orientations (Polat et al 2002;Pınar et al 2003), field geology (Altınok et al 2003;Seeber et al 2004;Okay et al 2004;Altunel et al 2004), paleoseismology (Rockwell et al 2001;Klinger et al 2003;McHugh et al 2006), Coulomb static stress change modelling (Hubert-Ferrari et al 2000;Parsons et al 2000;Utkucu et al 2003;Parsons 2004;Lorenzo-Martin et al 2006;Pondard et al 2007), space geodesy (Meade et al 2002;Flerit et al 2003) and earthquake probability (Parsons et al 2000;Parsons 2004;Cisternas et al 2004) studies. The basin of the Sea of Marmara was considered as a rift with a strike parallel to the proposed western Turkey rift system in the earlier phase of the construction of the plate kinematics of the eastern Mediterranean region (McKenzie 1972).…”
Section: Recent Seismotectonic Studiesmentioning
confidence: 99%
“…The thickness of the units varies from 50 to 200 m near the Yenisehir basin (TOPAL et al, 2003). The GIFZ zone corresponds to the NAFSS and has the potential to generate a strong earthquake (GULKAN et al, 1993;CISTERNAS et al, 2004). It extends from the east of Iznik Lake to the northern slopes of the UM along the Yenisehir plain (OZTURK et al, 2009).…”
Section: Geology and Tectonic Settingmentioning
confidence: 99%